2010
DOI: 10.1111/j.1365-2702.2010.03391.x
|View full text |Cite
|
Sign up to set email alerts
|

The Patient Care Delivery Model – an open system framework: conceptualisation, literature review and analytical strategy

Abstract: A better understanding of how factors in the work environment impact clinical outcomes can facilitate care processes in the nursing unit. Future studies using comprehensive conceptual frameworks and sophisticated analytical approaches will enhance professional nursing practice and improve clinical outcomes in healthcare organisations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 67 publications
(92 reference statements)
0
29
0
1
Order By: Relevance
“…); (2) patients’ age (O'Brien‐Pallas et al . , Fasoli et al . ); (3) direct workload retrieved from the activity recording for nursing ‘Leistungserfassung in der Pflege’ LEP ® (O'Brien‐Pallas et al .…”
Section: The Studymentioning
confidence: 99%
“…); (2) patients’ age (O'Brien‐Pallas et al . , Fasoli et al . ); (3) direct workload retrieved from the activity recording for nursing ‘Leistungserfassung in der Pflege’ LEP ® (O'Brien‐Pallas et al .…”
Section: The Studymentioning
confidence: 99%
“…created a model to describe the influence of hospital care structures and processes that influence mortality in acute medical patients and identified15 practice environment, staffing, and nurse characteristic variables but not nurse continuity. Two nurse-staffing models were found that included nurse continuity as a nurse-staffing variable 25–26 but neither were sufficient to describe the direct and moderating role of nurse continuity as my proposed model. The Irvine et al .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Continuity is not used as a nurse-staffing variable in this model but in reference to how nurses communicate and coordinate care with other health providers. The O’Brien-Pallas et al 26 model was the only model found that includes a relational nurse continuity variable within a depiction of 27 other patient, nurse, and system characteristics, and system behaviors that influence patient, nurse, and system outcomes. Continuity of care/shift change is included on a list of “Input” Systems Behavior that effect the Patient Care Delivery system (“throughput”) leading to patient, nurse and system outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Re‐sequencing brought on by unanticipated changes in the nurses' shift increases complexity as it requires additional time and energy, which is not the case with routine work (O'Brien‐Pallas et al . , , Thompson et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…changes to patients' conditions and nursing activities), which influence or transform output factors (patient, nurse and system outcomes) (O'Brien‐Pallas et al . , , Meyer et al . ).…”
Section: Introductionmentioning
confidence: 99%